Influence of the central venous site on the transpulmonary thermodilution parameters in critically ill burn patients. Issue 7 (November 2015) - Soussi, Sabri; Sisso, Fiona; Maurel, Véronique; Oueslati, Haikel; Legrand, Matthieu
Highlights The concordance was good for the CI and EVLW between jugular and ipsilateral femoral sites. Larger LOA for GEDVI might be related to the increased dilution volume of the boluses. The cross talk phenomenon was avoided when different lengths femoral catheters are used.